The Performance of Cold-Formed Steel Beam-Column Connections with Screw Configuration - Mohamed, Saker; Setyowulan, Desy; Arifi, Eva (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2024)
Cold-formed steel is being used as a viable substitute for traditional steel and building materials due to its performance, affordability, convenience, lightweight, and environmental friendliness. The major purpose of this current research is for a reaction to force-deformation at the connection level to be delivered, which is proper for typical cold-formed steel (CFS) screwed beam-column assembly CFS C-section, and to show the influence of the behavior of CFS under bending test. An inner plate, double angle plate, and self-drilling screws are used by a basic beam-column frame idealized CFS to join the beam-column. Fixed support was implemented at the column base, whereas the beam end had free support. A 0.75 mm cold-formed steel C-section with 80mm height and 30mm width was utilized in this study and assembled into an